2019
DOI: 10.1016/j.celrep.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan-Induced Trained Immunity Protects against Leishmania braziliensis Infection: a Crucial Role for IL-32

Abstract: American tegumentary leishmaniasis is a vectorborne parasitic disease caused by Leishmania protozoans. Innate immune cells undergo long-term functional reprogramming in response to infection or Bacillus Calmette-Gué rin (BCG) vaccination via a process called trained immunity, conferring nonspecific protection from secondary infections. Here, we demonstrate that monocytes trained with the fungal cell wall component b-glucan confer enhanced protection against infections caused by Leishmania braziliensis through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
113
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 68 publications
6
113
0
5
Order By: Relevance
“…Inducing both TII and adaptive immunity with a given vaccine strategy is expected to offer the best possible immune protection against the intended target pathogen while TII extends protection to a broad range of unrelated pathogens 84,85 . In this regard, keeping the current human vaccines and introducing new vaccines in human immunization programs with the known capability to induce TII will be of particular relevance to control pathogens of great health impact for which there has been a lack of effective human vaccines.…”
Section: Vaccine Concept and Strategies Respiratory Mucosal Vaccinatmentioning
confidence: 99%
“…Inducing both TII and adaptive immunity with a given vaccine strategy is expected to offer the best possible immune protection against the intended target pathogen while TII extends protection to a broad range of unrelated pathogens 84,85 . In this regard, keeping the current human vaccines and introducing new vaccines in human immunization programs with the known capability to induce TII will be of particular relevance to control pathogens of great health impact for which there has been a lack of effective human vaccines.…”
Section: Vaccine Concept and Strategies Respiratory Mucosal Vaccinatmentioning
confidence: 99%
“…Apart from metabolic and epigenetic regulation, the induction of trained immunity is also modulated at the level of signaling mechanism. It has been reported that trained immunity induced by β-glucan in monocytes is critically dependent on cAMP-PKA, IL-1, and IL-32 signaling induction (50,52). Using pharmacological blockade or functional genomic analysis, it was shown that disruption of cAMP-PKA or IL-1 signaling inhibits training capacity of monocytes while enhancing IL-32 expression accelerates β-glucan-induced trained immunity (50,52).…”
Section: β-Glucan-induced Training Programmentioning
confidence: 99%
“…It has been reported that trained immunity induced by β-glucan in monocytes is critically dependent on cAMP-PKA, IL-1, and IL-32 signaling induction (50,52). Using pharmacological blockade or functional genomic analysis, it was shown that disruption of cAMP-PKA or IL-1 signaling inhibits training capacity of monocytes while enhancing IL-32 expression accelerates β-glucan-induced trained immunity (50,52). Interestingly, IL-1 and IL-32 can promote the expression of each other in monocytes during β-glucan training, thus forming a self-reinforcing activating mechanism by which training effect of β-glucan can be enhanced (52).…”
Section: β-Glucan-induced Training Programmentioning
confidence: 99%
See 2 more Smart Citations